PRELIMINARY INVESTIGATIONS ON THE PIT CURING OF FISH IN INDIA - Suryanarayana Rao, S.V.; Rajendranathan Nayar, M.; Valsan, A.P. (Indian Journal of Fisheries, 2015)
Among the methods adopted for the curing of fish in India the practice of pit curing common in certain parts of the Madras State and the neighbouring region of Travancore is of considerable interest for several reasons. Broadly speaking the method consists in burying the fish after salting in mat lined pits for varying periods ranging from a few days to a fortnight or more before marketing in a partially dried condition without any further washing or drying. The products possess a distinct flavour and taste much appreciated by some sections of the public in the eastern parts of Madras State. However the process is mainly adopted by private curers outside the Government curing yards and the quality of the commercial samples leaves much to be desired due to their unwholesome appearance and commonly observed infestation with maggots (Krishna Pillai et ah, 1956). Since pit curing forms one of the main methods of curing around Mandapam, it was considered desirable to undertake a comprehensive investigation of the local practices relating to this cure and the keeping quality of the products.